COVID-19 impact on informal trade: Disruptions to livelihoods and food security in Africa - Bouët, Antoine; Kurtz, Julie E.; Traoré, Fousseini (International Food Policy Research Institute, 2020)
International trade of food and agricultural products plays a major role in ensuring food security and livelihoods across the African continent. Yet formal intracontinental trade data give only a glimpse of trade’s importance for African consumers and producers because—depending on the country and border—up to 99 percent of agricultural trade crosses borders informally. In West Africa, for example, an estimated 30 percent of staple foods evade formal customs, and the proportion can be much greater for highly perishable fruits and vegetables. Consequently, formal trade data paint only a limited picture of COVID-19’s disruptive effect on trade within the African continent—and of related nutrition and livelihood consequences. To better understand the current and future impacts on African food producers and consumers, we must examine both the magnitude and unique mechanisms of informal cross-border trade (ICBT).